Replication of an Association of a Promoter Polymorphism of the Dopamine Transporter Gene and Attention Deficit Hyperactivity Disorder - GILL, MICHAEL (Elsevier, 2009)
Genetic associations for Attention Deficit Hyperactivity Disorder (ADHD), a common highly heritable childhood behavioural disorder, require replication in order to establish whether they are true positive findings. The current study aims to replicate recent association findings from the International Multi-centre ADHD Genetics (IMAGE) project in one of the most studied genes related to ADHD, the dopamine transporter (DAT1) gene. In a family-based sample of 450 ADHD probands, three single nucleotide polymorphism (SNP) markers have been genotyped using TaqMan assays. Transmission Disequilibrium Test analysis demonstrates that one of three SNP markers (rs11564750) in the 5? promoter region of the gene is significantly associated with ADHD (P = 0.02). This provides further evidence that in addition to the well-known and investigated 3?UTR polymorphism associated with ADHD, there is potentially a further association signal emanating from the 5? promoter region of the gene. Further replication and functional studies are now required to fully understand the consequence of polymorphisms present at both the 5? and 3? ends of the DAT1 gene and their role in ADHD pathophysiology.
PUBLISHED
19576958
Keywords: ADHD; DAT1; Association; Replication; Polymorphism